2016
DOI: 10.1186/s12948-016-0041-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with food allergy

Abstract: Food allergy has increased in developed countries and can have a dramatic effect on quality of life, so as to provoke fatal reactions. We aimed to outline the socioeconomic impact that food allergy exerts in this kind of patients by performing a complete review of the literature and also describing the factors that may influence, to a greater extent, the quality of life of patients with food allergy and analyzing the different questionnaires available. Hitherto, strict avoidance of the culprit food(s) and use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 57 publications
1
64
0
6
Order By: Relevance
“…The prevalence of food allergies is on the rise, affecting nearly 4–6% of the population in the United States and impacting their daily life in various ways . The term food allergy refers to an adverse immune response to food proteins, which can be IgE‐mediated, non‐IgE‐mediated, or a combination of both .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of food allergies is on the rise, affecting nearly 4–6% of the population in the United States and impacting their daily life in various ways . The term food allergy refers to an adverse immune response to food proteins, which can be IgE‐mediated, non‐IgE‐mediated, or a combination of both .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the prevalence and incidence of allergic diseases have increased at different rates, [1][2][3] and they are associated with substantial medical and economic burdens to these patients. 4,5 Previous studies have demonstrated that both genetic and environmental factors play critical roles in the genesis and development of allergic diseases 6,7 Therefore, the prevalence of…”
Section: Introductionmentioning
confidence: 99%
“…Although several guidelines have been proposed for FA management in schools, minor allergic reactions and food-induced anaphylaxis have still occured 14. FA also has a negative influence on quality of life 15. In particular, schoolchildren are in a critical time for growth spurts and emotional changes.…”
Section: Introductionmentioning
confidence: 99%